Activation of lamina propria T cells induces crypt epithelial proliferation and goblet cell depletion in cultured human fetal colon. Issue 2 (February 1992) - Evans, C M; Phillips, A D; Walker-Smith, J A; MacDonald, T T
Abstract : An organ culture model has been used to study the effects of T cell activation in the human colon. Lamina propria T cells in explant cultures of human fetal colon (11 to 23 weeks gestation) were activated in situ using pokeweed mitogen or an anti-CD3 monoclonal antibody, and compared with unstimulated controls. After three days of culture, there was a two to four-fold increase in crypt epithelial cell proliferation in T cell stimulated explants of more than 15 weeks gestation, associated with a fall in crypt goblet cell numbers of up to 20-fold. By three days, the surface epithelium of stimulated explants appeared thin with loss of goblet cells, and by day 7, severe and extensive mucosal damage was observed by light and electron microscopy. These changes did not occur in control cultures and explants deficient in T cells (less than 16 weeks gestation), and were inhibited by cyclosporin A. These experiments indicate that the increase in epithelial cell proliferation and accompanying goblet cell depletion observed in colorectal crypts in chronic inflammatory bowel disease may be mediated by activated T cells.